PEMBINAAN KARAKTER DAN ETOS KERJA UNTUK MEMBANGUN SUMBER DAYA MANUSIA YANG UNGGUL DAN PROFESIONAL - Otistaviany, Heluny; Malik, Rusman; Sobirin (Kreativitas Pada Pengabdian Masyarakat (Krepa), 2024)
This study aims to analyze the effectiveness of character and work ethic development programs implemented by the Mu'thi Jaya Indonesia Foundation in shaping outstanding and professional human resources. Using a descriptive qualitative approach, data were collected through observation, in-depth interviews, and documentation analysis. The findings reveal that a participatory approach tailored to local needs successfully enhanced discipline, responsibility, and teamwork among participants. Continuous evaluation and collaboration with various community elements are key factors in the program's success. The applied development model can be replicated to support human resource development at national and global levels. Keywords: Character development, work ethic, human resources, education, professionalism.